2019
DOI: 10.1016/j.artd.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Unacceptable failure rate of a ceramic-coated posterior cruciate-substituting total knee arthroplasty

Abstract: Background Aseptic loosening is one of the most elusive problems in total knee arthroplasty. We compared the failure rates of posterior cruciate-substituting total knee arthroplasty utilizing implants with hardened surface coating to a previous cohort of patients who underwent the procedure with traditional cruciate-retaining noncoated cobalt-chrome implants. Methods A retrospective study was conducted of 1099 total knee arthroplasties performed from 2009 to 2017. Two h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…series an unacceptable failure rate of 6% prior to 1-year follow-up (15 aseptic loosenings out of a cohort of 249 TKAs implanted from 2015 to 2017) in comparison to a previously implanted cohort of 850 Columbus cruciate-retaining knees (2009-2014) with only 2 known revisions due to aseptic loosening (0.24%). They hypothesized that the new design of the Vega PS tibial tray may be a factor to be considered for their unfavorable clinical outcomes [48]. These findings are in contrast to the promising short-term clinical behavior of the Vega PS knee system reported by Jain et al [44].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…series an unacceptable failure rate of 6% prior to 1-year follow-up (15 aseptic loosenings out of a cohort of 249 TKAs implanted from 2015 to 2017) in comparison to a previously implanted cohort of 850 Columbus cruciate-retaining knees (2009-2014) with only 2 known revisions due to aseptic loosening (0.24%). They hypothesized that the new design of the Vega PS tibial tray may be a factor to be considered for their unfavorable clinical outcomes [48]. These findings are in contrast to the promising short-term clinical behavior of the Vega PS knee system reported by Jain et al [44].…”
Section: Discussionmentioning
confidence: 96%
“…For the ZrN multilayer-coated Vega PS knee system, Lionberger et al [48] reported in a retrospective study on a single surgeon case Fig. 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to this case series, previous studies have not been able to determine an exact etiology for the debonding. A range of possible hypotheses has been postulated including using HVC during the TKA, the specific cement application technique, and even the implant design [ [3] , [4] , [5] , [6] , [8] , [9] , [10] ]. The majority of these studies were published in the last 5 years and are not necessarily related to polyethylene wear (which may be a late factor in debonding cases).…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have linked certain implants as potential risk factors for implant-cement interface debonding in TKA [ 3 , 4 , 8 ]. For example, one retrieval analysis study of low-contact-stress mobile-bearing TKA found a negative correlation between the cement mantle thickness rates of debonding.…”
Section: Discussionmentioning
confidence: 99%